2019
DOI: 10.1159/000501428
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted versus Laparoscopic Distal Pancreatectomy: The Results of a Case-Matched Analysis from a Tertiary Care Center

Abstract: Background: Laparoscopic distal pancreatectomy (LDP) has been adopted relatively slowly despite the benefits of minimally invasive approach. The robotic approach can overcome the limitations of LDP, thus increasing the acceptance of minimally invasive distal pancreatectomy. Methods: We performed a 1: 1 retrospective case-matched comparison among 2 groups of 35 patients who underwent robotic-assisted distal pancreatectomy (RDP) or LDP from August 2014 to April 2017. Results: The operative time was similar in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…In robot-assisted distal pancreatectomy (RDP), the oncological outcomes of R0 resection rate and number of retrieved lymph nodes were comparable to those of laparoscopic and open DP. 93,[113][114][115][116] A study reported that the long-term prognosis associated with RDP, however, was significantly better than that associated with open DP. 116 In addition, the mortality rate and oncologic outcomes of robot-assisted pancreaticoduodenectomy (RPD) were comparable…”
Section: Robotic Pancreatectomymentioning
confidence: 99%
“…In robot-assisted distal pancreatectomy (RDP), the oncological outcomes of R0 resection rate and number of retrieved lymph nodes were comparable to those of laparoscopic and open DP. 93,[113][114][115][116] A study reported that the long-term prognosis associated with RDP, however, was significantly better than that associated with open DP. 116 In addition, the mortality rate and oncologic outcomes of robot-assisted pancreaticoduodenectomy (RPD) were comparable…”
Section: Robotic Pancreatectomymentioning
confidence: 99%
“…[ 20 21 22 23 24 ] The robotic approach has also been reported to be associated with superior spleen and splenic-vessel preservation rates compared to that of conventional laparoscopy. [ 25 26 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 19 ] Numerous studies have also compared robotic versus laparoscopic approaches for distal pancreatectomy, showing that the robotic approach is a safe and feasible alternative approach with comparable perioperative and oncological outcomes compared to that of the laparoscopic approach,[ 20 21 22 23 24 ] and may even have better spleen and vessel preservation rates. [ 25 26 ]…”
Section: Introductionmentioning
confidence: 99%
“…Splenectomy is associated with increased risks of infection and a In the era of advanced minimally invasive pancreatic surgery, some existing studies have shown equivalent outcomes of laparoscopic and robotic surgeries (10,23). However, compared to LDP, RDP shows advantages in both splenic and splenic vessel preservation (24,25). These advantages may be attributed to the high flexibility of robotic instruments and precise suturing both in the dissection of splenic vessels and in the control of bleeding of the splenic vessels.…”
Section: Discussionmentioning
confidence: 99%